SCARA5 Is Overexpressed in Prostate Cancer and Linked to Poor Prognosis - Fidelis Andrea Flockerzi; Johannes Hohneck; Matthias Saar; Rainer Maria Bohle; Phillip Rolf Stahl (Diagnostics, 2023)
Prostate cancer is one of the most common malignancies worldwide, showing a wide range of clinical behaviors. Therefore, several treatment options arise out of the diagnosis “prostate cancer”. For this reason, it is desirable to find novel prognostic and predictive markers. In former studies, we showed that THSD7A expression is associated with unfavorable prognostic parameters in prostate cancer and is linked to a high expression of focal adhesion kinase (FAK). Recently, scavenger receptor class A member 5 (SCARA5) was reported to be the downstream gene of THSD7A in esophageal squamous cell carcinoma. SCARA5 is believed to play an important role in the development and progression of several different tumor types. Most studies describe SCARA5 as a tumor suppressor. There is also evidence that SCARA 5 interacts with FAK. To examine the role of SCARA5 as a potential biomarker in prostate cancer, a total of 461 prostate cancers were analyzed via immunohistochemistry using tissue microarrays. Furthermore, we compared the expression level of SCARA5 with our previously collected data on THSD7A and FAK. High SCARA5 expression was associated with advanced tumor stage (p < 0.001), positive nodal status (p < 0.001) and high Gleason-score (p < 0.001). At least, strongly SCARA5-positive cancers were associated with THSD7A-positivity. There was no significant association between SCARA5 expression level and FAK expression level. To our knowledge, we are the first to investigate the role of SCARA5 in prostate cancer and we demonstrated that SCARA5 might be a potential biomarker in prostate cancer.